Optimization of cleaning process for castings - Ho, Audrey (2014)
Drilling and tapping processes are the most common processes in any manufacturing environment. These processes require a metal-working fluid (commonly known as coolant). It is applied at high pressure to remove the heat generated from the friction between the tool and workpiece. This is to ensure good surface finish on the workpiece and longer cutting tool life as well as to remove the chips formed during the process. As a result of this, coolant tends to get trapped in the tapped and/or drilled holes especially in the blind holes. This is more severe in castings that have higher permeability caused by porosity; an inherent property of die casting. Consequently, unsightly oil stains are being observed around the blind holes. This study focuses on removing the source of the stain, the phenomenon that causes the oil oozing out of the blind hole, and on the entire cleaning process for removing the trapped oil. The numerous parameters that could have significant effect on improving oil removal were studied through laboratory testing, design of experiments (DOE) and evaluations. With these results, the cleaning processes can be optimized to reduce oil stains. In addition, alternative cleaning technologies used by the same industry or other industries were studied.